Annual Plan, 1994-95 Volume II Government of Bihar - Planning Commission (Planning Commission, 1994)
Almost half the total area of the State consists of hills and plateaus, while the remaining half is an alluvial plain divided into two unequal parts, North and South, by the river Ganga. The State has, therefore, three well defined regions, viz, North Bihar, South Bihar and Chotanagpur Plateau covering an area of 0.54, 0.40 and 0.80 lakh sq. Kms., respectively. In 1981, the North Bihar Plains had a population of 31.5 millions with a density of 583 , the South Bihar Plains a population of 20.8 millions with a density of 520 and the Plateau area a population of 17.6 millions with a density of 220. In 1991, the population of these three regions increased to 40.1, 24.4 and 21.8 millions with density of population going upto 761, 609 and 273 respectively.
Government of Bihar, Planning Department